2022
DOI: 10.1073/pnas.2119907119
|View full text |Cite
|
Sign up to set email alerts
|

A unique bacterial secretion machinery with multiple secretion centers

Abstract: Significance The newly described type IX secretion systems (T9SSs) translocate virulence factors and can mediate specialized gliding motility among bacterial pathogens of the Fibrobacteres–Chlorobi–Bacterioidetes superphylum. We visualized the spatial organization of the T9SS in its native context in the Porphorymonas gingivalis cell by cryoelectron tomography. The T9SS exhibits distinct symmetries across the bacterial cell envelope: a cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…GldJ lipoprotein shares 30% identity with GldK lipoprotein over 382 amino acids 33 . P. gingivalis PorK (GldK homolog) with PorN makes a ring structure of ~8 nm in thickness and 52 nm in diameter 14 , 40 . The thickness of fibers in the multirail structure involving GldJ is almost the same as that of the PorK/PorN ring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GldJ lipoprotein shares 30% identity with GldK lipoprotein over 382 amino acids 33 . P. gingivalis PorK (GldK homolog) with PorN makes a ring structure of ~8 nm in thickness and 52 nm in diameter 14 , 40 . The thickness of fibers in the multirail structure involving GldJ is almost the same as that of the PorK/PorN ring.…”
Section: Discussionmentioning
confidence: 99%
“…T9SSs were first identified and studied in the nonmotile oral pathogen Porphyromonas gingivalis and in F. johnsoniae [8][9][10][11] . Recent studies have revealed that T9SS is a unique system that is clearly different from other secretion systems in terms of its supramolecular structure and secretion mechanism [12][13][14] . F. johnsoniae cells use the T9SS to secrete dozens of proteins, including soluble extracellular enzymes and motility adhesins that reside on the cell surface [15][16][17] .…”
mentioning
confidence: 99%
“…GldJ lipoprotein shares 30% identity with GldK lipoprotein over 382 amino acids 33 . P. gingivalis PorK (GldK homolog) with PorN makes a ring structure of ~ 8 nm in thickness and 52 nm in diameter 14,40 . It is worthy of note that the thickness of ber in the multi-rail structure involving GldJ is almost the same as that of the PorK/PorN ring.…”
Section: Discussionmentioning
confidence: 99%
“…T9SSs were rst identi ed and studied in the nonmotile oral pathogen Porphyromonas gingivalis and in F. johnsoniae [8][9][10][11] . Recent studies have revealed that T9SS is a unique system that is clearly different from other secretion systems in terms of its supramolecular structure and secretion mechanism [12][13][14] . F. johnsoniae cells use the T9SS to secrete dozens of proteins including soluble extracellular enzymes and motility adhesins that reside on the cell surface [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…PorK/GldK is an OM lipoprotein whereas PorN/GldN locates in the periplasm [13,21]. In Porphyromonas, the PorK and PorN proteins interact and assemble a 36-mer, 50 nm large ring [20,21]. This ring is located underneath the OM and is connected to 18 PorLM complexes via interactions between PorN and the PorM D4 domains, building an overall birdcage-like structure in the periplasm [13,16,20,25].…”
Section: The Om-associated Complexmentioning
confidence: 99%